High thermal conductivity and low electrical conductivity tailored in carbon nanotube (carbon black)/polypropylene (alumina) composites. (14th September 2016) - Xu, Ruijie; Chen, Minyi; Zhang, Feng; Huang, Xiaorui; Luo, Xiaogang; Lei, Caihong; Lu, Shengguo; Zhang, Xiaoqing
Abstract: In this paper, a stellated carbon filler (S-filler) through passivation of the surfaces of carbon nanotubes and carbon black (CNTs/CB) was fabricated, and the corresponding thermal conductive composites of polypropylene (blended with alumina) (PP/Al2 O3 ) incorporated with S-filler were fabricated. When adding 15 wt% S-filler, the composite shows an DC electrical resistivity as high as 8.34 × 10 11 Ω cm and high thermal conductivity about 0.68 W/m·k. The composite using the new carbon filler as hybrid part shows a higher thermal conductivity and electric insulation. The rheological test also shows that the percolation network is not formed by the S-filler. This work offers a novel route for the design of thermally conductive, but electrically insulative composites with polymer as a matrix.